Association of sleep behavior with depression: a cross-sectional study in northwestern China - Liu, Jingchun; Cao, Suixia; Huo, Yating; Liu, Huimeng; Wang, Yutong; Zhang, Binyan; Xu, Kun; Yang, Peiying; Zeng, Lingxia; Dang, Shaonong; Yan, Hong; Mi, Baibing (Frontiers in Psychiatry, 2023)
Background This study aimed to examine the association between sleep duration, sleep problems, and depression in Northwest China. Method Depression was diagnosed at the hospital and self-reported by the participants in the baseline survey. Sleep duration and problems, including difficulty initiating and maintaining sleep, early morning awakening, daytime dysfunction, use of sleeping pills or drugs, and any sleep problems, were obtained by a self-reported questionnaire. Logistic regression was used to estimate odds ratios (ORs) with corresponding 95% confidence intervals (CIs) for exploring the association between sleep duration, sleep problems, and depression, adjusting for demographic and socioeconomic characteristics and health behaviors. The association between depression and sleep duration was also evaluated continuously with restricted cubic spline curves based on logistic models. Results 36,515 adults from Regional Ethnic Cohort Study in Northwest China were included. About 24.04% of participants reported short sleep duration (<7 h), and 15.64% reported long sleep duration (≥9 h). Compared with standard sleep duration (7–9 h), short sleep duration was associated with a higher risk of depression (OR: 1.69, 95%CI: 1.26–2.27, p = 0.001). Self-reported sleep problems were also related to four times depression risk increased (OR: 4.02, 95%CI: 3.03–5.35, p < 0.001) compared with no sleep problems. In addition, a nonlinear relationship was found between sleep duration and depression after adjusting covariates (p = 0.043). Conclusion Sleep duration and sleep problems are associated with depression. Enough sleep time and healthy sleep habits in life course might be a practical health promotion approach to reduce depression risk in Northwest Chinese adults. A further study from cohort study is needed to verify the temporal association.